Cross-sectional study of the epidemiological profile and consequences of clandestine abortions among women in the city of Bunia, province of Ituri, northeast of the Democratic Republic of Congo - Lonema, Pascal M.; Mukandu, B. B. L.; Omanyondo, M. O. (Orapuh Journal, 2024)
Introduction Clandestine abortion remains a significant cause of maternal morbidity and mortality due to insufficient contraceptive services and restrictive Congolese legislation. Objective This cross-sectional study aims to identify the socio-demographic factors, methods, and health consequences of clandestine abortions among women in the City of Bunia, Ituri Province. Methods A sample of 118 cases of clandestine abortions was drawn from 1,514 pregnant women admitted to 5 health facilities selected through multi-stage sampling. Data were encoded and analysed in SPSS 20 using Fisher’s exact test. Results The study reveals a frequency of clandestine abortions of 7.78%. The women most affected were aged 15–19 years (45.45%), married girls (46.15%), primigravidae (60.0%), single women (64.14%), and displaced persons (50%). Nearly half of the research participants (49.15%) used misoprostol to induce abortion. The factors contributing to abortions included refusal of paternity (46.61%), fear of parents (29.66%), academic pursuits (18.64%), and rejection of pregnancy (5.08%). Retention of tissue was the most common complication, affecting more than one-third of the research participants (38.14%). Finally, 90% of the participants were cured, while 4.24% died. Conclusion In light of these findings, it is imperative to develop new multi-sectoral strategies aimed at promoting women’s empowerment, strengthening policies on access to contraceptive services, and engaging legal and religious leaders in discussions on sexual health law reform. Such measures could support efforts to combat clandestine abortions and ultimately contribute to the reduction of maternal mortality.